2020
DOI: 10.3390/ijms21176175
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminus Does Not Govern Protein Turnover of Schizosaccharomyces pombe CENP-A

Abstract: Centromere integrity underlies an essential framework for precise chromosome segregation and epigenetic inheritance. Although centromeric DNA sequences vary among different organisms, all eukaryotic centromeres comprise a centromere-specific histone H3 variant, centromeric protein A (CENP-A), on which other centromeric proteins assemble into the kinetochore complex. This complex connects chromosomes to mitotic spindle microtubules to ensure accurate partitioning of the genome into daughter cells. Overexpressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…In addition, histone modifications including activation markers (H3K4me1 and H3K4me3) and silencing marks (H3K27me3) at distal promoters were telomere length dependent, suggesting that the epigenetic state of telomere-distal promoters could be influenced by telomere length ( Mukherjee et al, 2018 ). Moreover, meiotic chromosome segregation is essential for the maintenance of genomic integrity of gametes and requires functional centromeres that are required for a precise epigenetic inheritance ( Mahlke and Nechemia-Arbely, 2020 ; Tan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, histone modifications including activation markers (H3K4me1 and H3K4me3) and silencing marks (H3K27me3) at distal promoters were telomere length dependent, suggesting that the epigenetic state of telomere-distal promoters could be influenced by telomere length ( Mukherjee et al, 2018 ). Moreover, meiotic chromosome segregation is essential for the maintenance of genomic integrity of gametes and requires functional centromeres that are required for a precise epigenetic inheritance ( Mahlke and Nechemia-Arbely, 2020 ; Tan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the functions of the N-terminal CENP-A are also reported for some species [16][17][18][19][20][21][22][23][24][25][26][27] (see also previous chapter, Sections 2.1, 2.2.2, 2.4.1, 2.9 and this chapter, Sections 2.1, 2.3, 2.4, 3.1, 4.1, 4.6, and 5.1). Loading of CENP-A at centromeres and its incorporation/deposition and maintenance in centromeric chromatin is cell cycle-regulated.…”
Section: Introductionmentioning
confidence: 69%
“…Domain-specific function, such as the N-terminal function, of fission yeast Cnp1/ CENP-A is also reported as budding yeast Cse4 [24,25] (see also previous chapter, Section 2.4). Folco et al demonstrated that alteration of the Cnp1 N-tail does not affect Cnp1 loading at centromeres, outer kinetochore recruitment, or spindle checkpoint signaling but significantly increases chromosome loss [17].…”
Section: Overview Of Cenp-a Cnp1mentioning
confidence: 88%
See 1 more Smart Citation
“…Their results using cse4KR mutants suggest that Psh1 is not the sole regulator of Cse4 proteolysis and that Doa1 facilitates Cse4 N-terminus-dependent proteolysis. We also note that N-terminal functions of CENP-A were described for some species [12,28,45,[47][48][49][50][51][52][53][54][55] (see also Sections 1.1, 1.4.1, 1.9 and next chapter, sections 2.1, 2.3, 2.4, 3.1, 4.1, 4.6, and 5.1).…”
Section: A Novel Role Of the N-terminus Of Cse4mentioning
confidence: 82%